Incidence and Characteristics of Patients with Visual Impairment due to Macular Edema Secondary to Retinal Vein Occlusion in a Representative Canadian Cohort - Robert J. Petrella; Julie Blouin; Brian Davies; Martin Barbeau (Journal of Ophthalmology)
Retinal vein occlusion (RVO) is an obstruction of the retinal venous system, and macular edema (ME) is a complication of RVO that can lead to blindness. The Canadian incidence of visual impairment (VI) due to ME secondary to RVO is unknown. This observational, retrospective study used records from the Southwestern Ontario database to observe the annual incidence, demographics, and comorbidity characteristics of patients with VI due to ME secondary to RVO. From 47,166 patients, 73 with RVO (>40 years old) were identified: 53 with branch retinal vein occlusion (BRVO), 20 with central retinal vein occlusion (CRVO). The annual incidence of VI (visual acuity <20/40 in Snellen equivalent) due to ME secondary to BRVO was (mean (95%CI)) 0.056% (0.011–0.072), and to CRVO was 0.021% (0.008–0.081). Furthermore, a greater proportion of RVO patients had hypertension (68% versus 14%) or dyslipidemia (16% versus 10%), when compared to a healthy control cohort of 76,077 subjects (P<0.05). This study presents a description of the characteristics of patients with VI due to ME secondary to RVO in a real-world Canadian setting. The results demonstrate that BRVO was more frequent than CRVO, and that RVO in this patient population was associated with several vascular comorbidities.